GREEN TECHNOLOGY-ORIENTED INVESTMENTS – ACHIEVING SUSTAINABLE DEVELOPMENT THROUGH THE IT SECTOR - Sabina Kholiyorovna Bo‘tayeva (American Journals, 2025)
This article analyzes the role of investments in green technologies in achieving sustainable development through the information technology sector. The IT sector is considered a crucial factor in increasing energy efficiency, reducing waste, and ensuring environmental sustainability through innovative solutions. The article discusses best practices, challenges, and solutions to improve investment efficiency.
Keywords: Green technologies, information technology, sustainable development, investments, energy efficiency, environmental innovation.